Developing Teachers’ Job Satisfaction in Jilin, China - Shen, Yifei (Scholar: Human Sciences, 2025)
Purpose: This study aims to investigate the independent variables that affect the job satisfaction of teachers at a private foreign language university in Jilin Province, China, and to propose strategies for improvement to enhance the quality of education and promote educational reform. Research design, data, and methodology: The study employed a questionnaire survey of 90 full-time teachers, covering aspects such as spirituality, teaching competency, core evaluations, school effectiveness, self-efficacy, and adaptive space. To ensure the validity of the questionnaire content, the Index of Item-Objective Congruence methodology was utilized to scrutinize each question, ensuring that it appropriately and validly measured various aspects of job satisfaction among university teachers. Following this, 30 full-time lecturers underwent a 20-week Strategic Plan. Afterward, the quantitative results from post-SP and pre-SP were analyzed in the paired-sample t-test for comparison. Results: The study’s findings supported two hypotheses: teaching competency and core evaluations significantly affect teachers’ job satisfaction, while the other four were rejected. Finally, the results from the paired-sample t-test for comparison demonstrated significant differences in both teaching competency and core evaluations between the post-SP and pre-SP stages. Conclusions: The results provide a theoretical basis and practical guidance for higher education institutions to develop effective strategies to enhance teachers’ job satisfaction and advance educational reform.